Matematyka
mati1122a
2017-06-24 10:06:07
30. Wykonaj działania:
Odpowiedź
zdzislawzimolag
2017-06-24 16:46:14

[latex]a) (5+sqrt{7})-(3+2sqrt{7}) = 5+sqrt{7}-3-2sqrt{7}=2 - sqrt{7}\\b) (a+bsqrt{c})+(a-bsqrt{c}) = a+bsqrt{c}+a-bsqrt{c} = 2a\\c) (5+2sqrt{7})+(3 -4sqrt{7}) = 5+2sqrt{7}+3-4sqrt{7} = 8-2sqrt{7}\\d) (frac{3}{7}-sqrt{5})+(frac{1}{14}+2sqrt{5}) = frac{6}{14}-sqrt{5}+frac{1}{14}+ 2sqrt{5}=frac{7}{14}+sqrt{5} = frac{1}{2}+sqrt{5}[/latex] [latex]e) (10-3sqrt{3})+(4+4sqrt{3}) = 10-3sqrt{3}+4+4sqrt3} = 14+sqrt{3}\\f) (a+bsqrt{c})-(a-bsqrt{c}) = a+bsqrt{c}-a+bsqrt{c} = 2bsqrt{c}\\g) frac{4}{9}+(-1+2sqrt{13}) = frac{4}{9}-frac{9}{9}+2sqrt{13} =2sqrt{13}-frac{5}{9}\\h) (1,15 + sqrt{10})+2sqrt{10} = 1,15 + sqrt{10}+2sqrt{10} = 1,15 + 3sqrt{10}[/latex]

Dodaj swoją odpowiedź